Efecto del extracto Etanólico de hojas de Piper angustifolium Matico sobre el crecimiento de Proteus mirabilis en condiciones de laboratorio - Zavaleta Castro, Linda Cristina (2018)
Abstract The objective of the present investigation was to determine the effect of the ethanolic extract concentrations of Piper angustifolium leaves "matico" on the growth of Proteus mirabilis under laboratory conditions. To obtain the ethanolic extracts of leaves of P. angustifolium "matico", 38 g of leaf powder were distilled in the soxlet equipment with 200 ml of 95% ethanol, the obtained distillate was dried with thermal air and all the obtained it was diluted in 10 ml of twenn 80%, obtaining a stock solution, then dilutions were made (10, 15, 20, 25 and 30 mg / ml). The inoculum of P. mirabilis was prepared with a turbidity level of tube No. 0.5 on the Mc Farland scale and was seeded on Muller Hinton agar; To evaluate the effect of the extract, the method originally described by Kirby-Bauer with Watman No. 4 paper discs of 7mm diameter was used in which 30 ul of each extract dilution was injected, then dried at 30 ° C, then 5 discs were placed per plate: 3 discs with the same dilution, plus a positive control (ciprofloxacin disc) and a negative control (disc impregnated in Twenn) on the surface of the sown plates, the same ones that were incubated 37ºC for 24 hours, after this time, the diameters (mm) of the inhibition zones were measured. The results show the significant differences between the different concentrations of the extract used against the microorganism tested. The effect of the ethanolic extract of the leaves of P. angustifolium was increasing as the concentration was increased, obtaining an inhibition halo of up to 10 mm in the concentration of 10 mg / ml and up to 18.7 mm in the concentration of 30 mg / ml , this would be due to the flavonoids would produce the inhibition of the growth of P. mirabilis. Key